Comparing cognitive load and self-regulatory depletion: Effects on emotions and cognitions. (October 2017) - Maranges, Heather M.; Schmeichel, Brandon J.; Baumeister, Roy F.
Abstract: Prior research has found both similar and different effects of self-regulatory resource depletion and cognitive load. To resolve these seeming contradictions, we experimentally compared the effects of cognitive load and self-regulatory depletion. Ego depletion led participants to pay more attention to pain and to persist less on a pain test, whereas load had opposite effects (Study 1). Load distracted people from processing and reacting to negative emotional content of pictures (Study 2), and boosted positive feelings even without an overt emotion induction (Study 3), whereas depletion did not change how people felt relative to control. Depletion and load had equivalent null effects on visual recognition memory (Study 2) but different effects on semantic processing involving emotional connections (Study 3). Taken together, results suggest that load distracts attention away from, whereas ego depletion undermines top-down control over the processing of pain and negatively-valenced content. We discuss implications for learning and instruction. Highlights: We empirically compared the effects of cognitive load and depletion. Load, but not depletion, decreased negative and boosted positive feelings. Both had null on visual memory but different effects on semantic processing. Cognitive load distracts away from negative physical and emotional feelings. Ego depletion undermines top-down control over implicit emotional processes.